The epidemiology of rotavirus disease in under-five-year-old children hospitalized with acute diarrhea in central Uganda, 2012-2013 - Bwogi, Josephine; Malamba, Samuel; Kigozi, Brian; Namuwulya, Prossy; Tushabe, Phionah; Kiguli, Sarah; Karuhize Byarugaba, Denis; Desselberger, Ulrich; Iturriza-Gomara, Miren; Karamagi, Charles (Archives of virology, 2016)
A cross-sectional study was undertaken during 2012-2013 to determine the prevalence, strains and factors associated with rotavirus infection among under-5-year-old children hospitalized with acute diarrhea in Uganda. Rotaviruses were detected in 37 % (263/712) of the children. The most prevalent strains were G9P[8] (27 %, 55/204) and G12P[4] (18.6 %, 38/204). Mixed infections were detected in 22.5 % (46/204) of the children. The study suggests that consumption of raw vegetables (OR = 1.45, 95 % CI = 1.03-2.03) and family ownership of dogs (OR = 1.9, 95 % CI = 1.04-3.75) increases the risk of rotavirus infection. The study findings will be used to assess the impact of RV vaccination in Uganda.
Keywords: Rotavirus; Genotyping; Mixed infections; Reassortment; Food hygiene; Zoonotic transmission